Central Bank Independence and Inflation in Latin America-Through the Lens of History - Jacome, Luis.; Pienknagura, Samuel (Washington, D.C. : International Monetary Fund, 2022)
We study the link between central bank independence and inflation by providing narrative and empiricial evidence based on Latin America's experience over the past 100 years. We present a novel historical dataset of central bank independence for 17 Latin American countries and recount the rocky journey traveled by Latin America to achieve central bank independence and price stability. After their creation as independent institutions, central bank independence was eroded in the 1930s at the time of the Great Depression and following the abandonement of the gold exchange standard. Then, by the 1940s, central banks turned into de facto development banks under the aegis of governments, sawing the seeds for high inflation. It took the high inflation episodes of the 1970s and 1980s and the associated major decline in real income, and growing social discontent, to grant central banks political and operational independence to focus on fighting inflation starting in the 1990s. The empirical evidence confirms the strong negative association between central bank independence and inflation and finds that improvements in independence result in a steady decline in inflation. It also shows that high levels of central bank independence are associated with reductions in the likelihood of high inflation episodes, especially when accompanied by reductions in central bank financing to the central government.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Government and the Monetary System; Monetary Systems; Payment Systems; Regimes; Standards